Direct measurement of local oxygen concentration in the bone marrow of live animals - Spencer, Joel A.; Ferraro, Francesca; Roussakis, Emmanuel; Klein, Alyssa; Wu, Juwell; Runnels, Judith M.; Zaher, Walid; Mortensen, Luke J.; Alt, Clemens; Turcotte, Raphaël; Yusuf, Rushdia; Côté, Daniel; et al. (Nature (London), 2014)
Here, using two-photon phosphorescence lifetime microscopy, the local oxygen tension in the bone marrow of live mice is found to be quite low, with spatiotemporal variations depending on the blood vessel type, distance to the endosteum, and changes in cellularity after stress. Oxygen tension in live bone marrow Low oxygen tension (hypoxia) is commonly thought to be a shared niche characteristic in maintaining quiescence in many stem cell types. However, local oxygen concentration, for example in the bone marrow, has never been measured directly. Charles Lin and colleagues have now developed a method based on two-photon microscopy to measure the absolute local oxygen tension ( p O 2 ) in the marrow of live animals. Using this method, they found that while vascular density is high throughout the bone marrow, overall oxygenation is quite low and there is heterogeneity in local p O 2 with respect to vessel type and location. For example, surprisingly, the endosteal region is not the region of the lowest p O 2 . After radiation or chemotherapy, bone marrow p O 2 becomes elevated and transplanted haematopoietic stem/progenitor cells do not seek out regions with the lowest p O 2 for homing. Characterization of how the microenvironment, or niche, regulates stem cell activity is central to understanding stem cell biology and to developing strategies for the therapeutic manipulation of stem cells 1 . Low oxygen tension (hypoxia) is commonly thought to be a shared niche characteristic in maintaining quiescence in multiple stem cell types 2 , 3 , 4 . However, support for the existence of a hypoxic niche has largely come from indirect evidence such as proteomic analysis 5 , expression of hypoxia inducible factor-1α ( Hif-1 α) and related genes 6 , and staining with surrogate hypoxic markers (for example, pimonidazole) 6 , 7 , 8 . Here we perform direct in vivo measurements of local oxygen tension ( p O 2 ) in the bone marrow of live mice. Using two-photon phosphorescence lifetime microscopy, we determined the absolute p O 2 of the bone marrow to be quite low (<32 mm Hg) despite very high vascular density. We further uncovered heterogeneities in local p O 2 , with the lowest p O 2 (∼9.9 mm Hg, or 1.3%) found in deeper peri-sinusoidal regions. The endosteal region, by contrast, is less hypoxic as it is perfused with small arteries that are often positive for the marker nestin. These p O 2 values change markedly after radiation and chemotherapy, pointing to the role of stress in altering the stem cell metabolic microenvironment.